Social Work in Palestine: Between the reality of education and the absence of professional practice - Shpeita, Zardah Hassan; Abdelrazek, Kawther Ribhi (Journal of Humanities & Social Sciences, 2020)
The current working paper aimed to identify the reality of social service in Palestine, in terms of its education and the reality of its professional practice, within the social institutions operating in Palestine, where the two researchers addressed a set of basic axes, through a comprehensive presentation and clarification of the concept of education and practice of social service, and the reality of the origin of its education In Palestine, and the need for Palestinian society to exist, to find a way to practice it in Palestine. The two researchers concluded, through analysis and discussion, that there is an absence of practical professional practice in these Palestinian institutions, due to many reasons, including There is no specialized practice in these institutions. Whereas, these institutions practicing professional work are not dependent on theoretical frameworks, and without knowledge of methods of professional intervention, and the weakness and scarcity in the practice of working with individual cases, and working with groups and societies, in the absence of material and human capabilities. At the end of the scientific paper, several recommendations were made by the two researchers in the absence of professional practice; It was represented by the necessity of working to expand the base of relying on research and field studies, and using its results in drawing plans and social projects in the Palestinian community, in addition to increasing the number of faculty members in Palestinian universities who specialize in teaching social service in accordance with the foundations and modern scientific methods, including helping this to provide learners with the most important scientific methods of professional practice, and students transfer them to these social institutions, to improve their work style, and practice them within the Palestinian reality, which is in urgent need of proper professional intervention.